Meta analisis intervensi psikoterapi interpersonal untuk menurunkan depresi - Angelica, Karina; Yudiarso, Ananta (Universitas Brawijaya, 2022)
Depression is a common mental disorder and has been causing many cases of death by suicide. The present study examines the effectiveness of the interpersonal psychotherapy approach against depression by conducting a meta-analysis. Specifically, we investigated 12 international articles involving 848 participants. Data analysis took account the number of participants (N), mean (M), and standard deviation (SD) of the post-treatment results for the experimental (treated with interpersonal psychotherapy) and control groups (did not receive treatment or treated by other therapies). The results showed the effectiveness of interpersonal psychotherapy in reducing depression. Keywords: depression, interpersonal psychotherapy, meta-analysis